Indirect determination of formaldehyde in fish by fluorescence spectroscopy - Aimi Syukran Kamarudin, 1988-; Azli Sulaiman, supervisor; Fakulti Sains (2010)
Project Paper (Sarjana Muda Sains (Kimia)) - Universiti Teknologi Malaysia, 2010